American force dangers, delusions, and dilemmas in national security - Betts, Richard K. 1947- (Columbia University Press, 2013)
While American national security policy has grown more interventionist since the Cold War, Washington has also hoped to shape the world. Misled by the stunning success against Iraq in 1991, administrations of both parties have pursued ambitious aims with limited force, committing the country's military frequently with inconsistent justification. These ventures have produced strategic confusion, unplanned entanglements, and indecisive results. This collection of essays by Richard K. Betts investigates use of American force since end of Cold War, suggesting guidelines for making it more selective and successful. Betts brings his knowledge of twentieth century American diplomatic and military history to bear on full range of theory and practice in national security, surveying Cold War roots of recent initiatives and arguing U.S. policy has been more unilateral than liberal theorists claim. He exposes mistakes made by humanitarian interventions and peace operations; reviews issues raised by terrorism and use of modern nuclear, biological, and cyber weapons; evaluates case for preventive war, which almost always proves wrong; weighs lessons learned from campaigns in Iraq, Afghanistan, and Vietnam; assesses rise of China and resurgence of Russia; quells concerns about civil-military relations; exposes anomalies within recent defense budgets; and confronts practical barriers to effective strategy. Betts ultimately argues for greater caution and restraint, while encouraging more decisive action when force is required, and recommends a more dispassionate assessment of national security interests, despite global instability and unfamiliar threats